Accurate Identification of Infection Source in Burn Trauma Patients With Central Line Infection to Determine Appropriate Treatment Option As Well As Proper Public Reporting. Issue 1 (January 2017) - Hampe, Holly M.; Graper, Lisa; Hayes-Leight, Kathy; Olszewski, Deborah; Moffa, Matthew; Bremmer, Derek N.
Abstract : With the advent of the Patient Safety Movement in the late 1990s and the CMS (Centers for Medicare & Medicaid Services) nonreimbursement program for never events, there has been much focus on the prevention and accurate identification of health care–associated infections such as central line–associated bloodstream infections (CLABSIs). There has certainly been a national effort to decrease the occurrence of these infections. With the implementation of patient safety initiatives such as the central line prevention bundle, there has been a considerable reduction in the number of CLABSIs except for patients with burn trauma. Because of the compromised nature of these patients, the number of CLABSIs has not decreased similarly to other types of patients. In addition, these patients may have a secondary infection that was not accurately or timely identified. With CLABSIs, proper identification of primary and secondary infections is very important, particularly when identifying treatment options and ensuring accurate public reporting of health care–associated infection information.